Japońska teoria krajobrazu (fūkeiron) jako źródło inspiracji - Loska, Krzysztof (Przestrzenie Teorii, 2025)
Starting from the theoretical concept of Masao Matsuda, who wrote about the landscape in the context of political power to draw attention to the homogenization of space and the violence of state apparatuses, I intend to consider the influence that the Japanese theory (fūkeiron) had on contemporary visual art. The point of reference is the work of Éric Baudelaire, French American director and multimedia artist who developed the approach proposed by Masao Matsuda and Masao Adachi. In his films and installations, he showed how the transformation of space relates to the oppressive system of power. The subject of the analysis are two documentaries: The Anabasis of May and Fusako Shigenobu, Masao Adachi & 27 Years without Images (2011) and Also Known as Jihadi (2017).